Clinic and genetic predictors in response to erenumab - Zecca, Chiara; Cargnin, Sarah; Schankin, Christoph; Giannantoni, Nadia Mariagrazia; Viana, Michele; Maraffi, Isabella; Riccitelli, Gianna Carla; Sihabdeen, Shairin; Terrazzino, Salvatore; Gobbi, Claudio (European journal of neurology, 2022)
Background and purpose Erenumab (ERE) is the first anticalcitonin gene‐related peptide receptor monoclonal antibody approved for migraine prevention. A proportion of patients do not adequately respond to ERE. Methods Prospective multicenter study involving 110 migraine patients starting ERE 70 mg monthly. Baseline socio‐demographics and migraine characteristics, including mean monthly migraine days (MMDs), migraine‐related burden (MIDAS [Migraine Disability Assessment scale] and Headache Impact Test‐6), and use of abortive medications, during 3 months before and after ERE start were collected. Real‐time polymerase chain reaction was used to determine polymorphic variants of calcitonin receptor‐like receptor and receptor activity‐modifying protein‐1 genes. Logistic regression models were used to identify independent predictors for 50% responder patients (50‐RESP) and 75% responder patients (75‐RESP). Results At month 3, MMDs decreased from 17.2 to 9.2 (p < 0.0001), 59/110 (53.6%) patients were 50‐RESP, and 30/110 (27.3%) were 75‐RESP. Age at migraine onset (odds ratio [OR] [95% confidence interval (95% CI)]: 1.062 [1.008–1.120], p = 0.024), number of failed preventive medications (0.753 [0.600–0.946], p = 0.015), and MIDAS score (1.011 [1.002–1.020], p = 0.017) were associated with 75‐RESP. Among the genetic variants investigated, RAMP1 rs7590387 was found associated with a lower probability of being 75‐RESP (per G allele OR [95% CI]: 0.53 [0.29–0.99], p = 0.048]), but this association did not survive adjustment for confounding clinical variables (per G allele, 0.55 [0.28–1.10], p = 0.09]). Conclusions In this real‐word study, treatment with ERE significantly reduced MMDs. The number of failed preventive medications, migraine burden, and age at migraine onset predicted response to ERE. Larger studies are required to confirm a possible role of RAMP1 rs7590387 as genetic predictor of ERE efficacy. Clinical predictors of a 75% or higher reduction in monthly migraine days during 3‐month erenumab treatment were older age at migraine onset, lower number of failed preventive medications, and higher migraine burden as measured by the Migraine Disability Assessment score questionnaire. At multivariate analysis, no single nucleotide polymorphisms (SNPs) at calcitonin receptor like receptor (CALCRL) and RAMP1 were found to be an independent predictor of treatment response, despite a modest effect of SNPs cannot be ruled out due to the limited sample size of our study.